2018
DOI: 10.21037/cco.2018.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine therapy for ER-positive/HER2-negative metastatic breast cancer

Abstract: The estrogen receptor (ER) has been targeted for breast cancer treatment for over a century, but many challenges persist. ER-positivity identifies the largest breast cancer subgroup, and ER-directed therapies prolong survival and improve symptoms in the advanced setting with a very favorable side effect profile. Treatment strategies have included decreasing estrogen synthesis and modulating or degrading the ER. However, ER+ breast cancer once diagnosed in the advanced setting still represents an incurable cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Tamoxifen is the most commonly used SERM treatment and is mostly recommended for premenopausal women (38). It has shown a 31% reduction in the five-year mortality rate among hormone receptor-positive women (39) and around 500,000 women are alive today as a result of tamoxifen therapy alone (40). Aromatase inhibitors are competitive inhibitors of the aromatase enzyme and inhibit the synthesis of estrogen.…”
Section: Endocrine Therapy and Mechanism Of Actionmentioning
confidence: 99%
“…Tamoxifen is the most commonly used SERM treatment and is mostly recommended for premenopausal women (38). It has shown a 31% reduction in the five-year mortality rate among hormone receptor-positive women (39) and around 500,000 women are alive today as a result of tamoxifen therapy alone (40). Aromatase inhibitors are competitive inhibitors of the aromatase enzyme and inhibit the synthesis of estrogen.…”
Section: Endocrine Therapy and Mechanism Of Actionmentioning
confidence: 99%
“…We are currently moving toward the era of personalized treatment, which is why knowledge regarding TNM stage and histopathological grading alone, although it supplies independent prognostic information, is inadequate for optimum patient treatment. Consequently, molecular biomarkers, such as ER and PR status, can provide prognostic information and additionally predict the response to therapy, and they have therefore become the center of research [7,33,34,35,36,37,38,39,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these regimes are currently, according to National Comprehensive Cancer Network (NCCN) guidelines, an indispensable part of the adjuvant therapy for women with hormone receptor-positive (HR+) BC [2,3]. Clinical studies have confirmed that a high HR expression, such as estrogen receptor (ER), progesterone receptor (PR), and vitamin D receptor (VDR), increases the course of the disease [4,5,6,7,8]. In this study, we decided to further investigate the above-mentioned HR expressions, all being nuclear receptors, activated by their steroid hormones and being important targets for both prevention and treatment of BC.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapy regimes led to a decline in the BC-associated mortality rate of approximately 30%, which makes them indispensable for the treatment of hormone-receptor-positive (HR+) BC [9][10][11]. Furthermore, clinical trials indicate a strong correlation between the expression of "classical steroid hormone receptors", such as ER and PR, and the progression of the disease [12][13][14][15][16]. Nevertheless, some tumors are resistant to those established therapeutic options, so the identification of new therapeutic targets is consequently central to research interests [17].…”
Section: Introductionmentioning
confidence: 99%